X subtracted from y means y-x
(4x^2-4x+3)-(2x^2-6x-4)
4x^2-4x+3-2x^2+6x+4
4x^2-2x^2-4x+6x+3+4=
2x^2+2x+7
<span>y in (-oo:+oo)
(3*y+6)/11 = -9 // + 9
(3*y+6)/11+9 = 0
(3*y+6)/11+(9*11)/11 = 0
3*y+9*11+6 = 0
3*y+105 = 0
(3*y+105)/11 = 0
(3*y+105)/11 = 0 // * 11
3*y+105 = 0
3*y+105 = 0 // - 105
3*y = -105 // : 3
y = -105/3
y = -35
y = -35</span>
∛(1/8 - <em>x</em>) = -1/2
Take the 3rd power of both sides and solve:
(∛(1/8 - <em>x</em>))³ = (-1/2)³
1/8 - <em>x</em> = -1/8
2/8 = <em>x</em>
<em>x</em> = 1/4
Answer:
china
Step-by-step explanation:
tssysystattatzfkfkvkgkfusudirudud
Answer:
2045
Step-by-step explanation:
-34×12(-5)+5
-405(-5)+5
2040+5
2045 is the answer